Small Intestinal Bacterial Overgrowth (SIBO): Result of Altered Defensive Mechanism in Gastrointestinal – A Review - Alvin Hartanto Kurniawan; Vania Azalia Gunawan; Benedictus Hanjaya Suwandi; Ulfa Kholili (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2020)
Small intestinal bacterial overgrowth (SIBO) is a condition that is characterized by an increased number of bacteria in the small intestine or an existence of bacteria type that generally should not be in the small intestine. In SIBO, the number of bacteria found in culture was more than 105 CFU (Colony-Forming unit) per ml. The fundamental problem in which SIBO occurred was the disruption in defensive mechanisms to prevent bacteria from overgrowing, including gastric acid juice, intestine motility, competent immune function, and intact anatomy. Disruption of this defensive mechanism will lead to SIBO, which furthermore will result in not only mild complications, such as abdominal complaints, but also severe complications, such as maldigestion/malabsorption, nutrient deficiency, or even systemic infection and acidosis. The manifestations of SIBO were often unclear so that it is hard to distinguish with other diseases, which much lead to misdiagnosis or underdiagnosis. Diagnosis of SIBO should be conducted very meticulously regarding underlying diseases that resulted in gastrointestinal defensive mechanism disturbance and malassimilation syndrome. Additional examinations for SIBO currently were jejunal aspiration and breath test, but both of them had their limitations in sensitivity and specificity. Therapeutical management consisted of treating the underlying diseases, eradicating bacteria with the antibiotic, particularly rifaximin, and improving nutritional deficiency.